Peran Efikasi Diri dalam Pekerjaan terhadap Keseimbangan Pekerjaan dan Keluarga pada Karyawan - Lifthya Ahadiati Akmala; Malida Fatimah (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2021)
The challenge to balance the roles between work and family for employees is influenced by various factors ranging from organizational and individual aspects. Occupational self-efficacy is an individual factor that predict of work-family balance. The purpose of this study is to empirically examine the relationship between work-family balance with occupational self-efficacy. This study uses two instruments including the work-family balance scale and occupational self-efficacy scale. Partisipants in this study were 138 employees. The results of the Spearmen Rho’s analysis showed that occupational self-efficacy had a significant correlation with work-family balance (p=0.00, p0.05).